INDONESIA'S CHALLENGES AND STRATEGIES FOR THE ASEAN ECONOMIC COMMUNITY (AEC) - Nurhayati, Dr. Dies (Srawung: Journal of Social Sciences and Humanities, 2022)
The challenges Indonesia faces in the ASEAN economic integration process are not only internal but also include competition between ASEAN countries and other nations outside the region. Another significant challenge is Indonesia's inflation rate, which remains higher than that of other ASEAN countries. Several fundamental issues need to be addressed in response to the ASEAN Economic Community (AEC) 2015. Indonesia struggles with a high rate of hidden unemployment, while low-level entrepreneurs play a crucial role in expanding job opportunities. Additionally, a large portion of Indonesian workers are uneducated and have low productivity, while the number of educated unemployed individuals continues to rise. Productivity disparities, the dominance of the informal sector, and the highest unemployment rate among the 10 ASEAN countries further compound the problem. Other pressing concerns include issues related to minimum wage, contract labor, employment conditions, and social insurance, as well as the challenges faced by Indonesian workers abroad. Given these challenges, the government must take immediate strategic steps to address the threats posed by the AEC. This can be achieved by formulating and reforming national policies aimed at enhancing the competitiveness of human resources and industries.